Implementasi Pancasila sebagai Sumber dari Segala Sumber Hukum dalam Pendidikan Pesantren dan Madrasah Dinniyah - Mulia Syarifatuzzahra; Ahmad Muhammad Mustain Nasoha; Altra Slashearly Ryanlista Firstly; Afri Khoirunnisa; Fika Alda Faruzia; Tan Hana Salma Rahmatullah (Majelis: Jurnal Hukum Indonesia, 2025)
Pancasila, as the state foundation and the source of all sources of law, has a strategic role in shaping the national education system, including religious-based institutions such as pesantren (Islamic boarding schools) and madrasah diniyah (non-formal Islamic religious schools). This study aims to examine how Pancasila values are internalized into the curriculum, school regulations, and educational practices of pesantren and madrasah diniyah. The research uses a qualitative approach with a library study design. Data were obtained from literature, journals, regulations, and official documents. The findings show that Pancasila provides a normative foundation for the development of pesantren education regulations and serves as an ethical guideline for shaping students’ character. The values of divinity, humanity, unity, deliberation, and social justice are reflected in educational practices, although the implementation is often influenced by local culture and the autonomy of pesantren. In conclusion, Pancasila functions not only as the basic legal norm but also as a source of inspiration for moral and civic education in pesantren and madrasah diniyah.